WEBINAR INTERNASIONAL TENTANG PENGELOLAAN SAMPAH RUMAH TANGGA STUDI KASUS DI KOTA DEPOK - Irfandi, Ahmad; Veronika, Erna; Azteria, Veza; Kusumaningtiar, Devi Angeliana; Nitami, Mayumi (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Waste is a persistent problem in Indonesia because there are no strict sanctions for perpetrators who throw rubbish carelessly. This international webinar activity aims to increase participants understanding of household waste management. This activity consists of three stages, namely a speech, presentation of material by speakers 1 and 2 and discussion and questions and answers. The participants in this activity came from university students from countries in ASEAN. The number of participants who attended was 19 people. This activity ran successfully and smoothly and provided benefits to the people of ASEAN. The results of this activity are expected to increase public knowledge about waste management in households and initiate waste management movements in their respective areas.